Slot die coating of lithium-ion battery electrodes - Schmitt, Marcel (KIT Scientific Publishing, 2016)
The Li-ion battery technology could help to accelerate the transition towards renewable energy sources. In the manufacturing chain, the electrode processing by slot die coating is one of the most crucial steps. Increased line speeds and reduced scrap rates could help decrease these costs. The scope of this work is therefore the scientific elaboration of the process limits of single and subdivided, simultaneous coated multilayer films, a minimizing of edge effects and intermittent coatings.